Peran Masyarakat Desa Bugel dalam Menjaga Tradisi Gotong Royong - Alfina, Sefa Rega (Javano Islamicus, 2026)
Mutual cooperation is a cultural value that has long been ingrained in Indonesian society. This value plays a very important role in building social solidarity and cooperation among citizens. However, with the development of the times and the tide of modernization, cultural values such as mutual cooperation have begun to change, and in some cases even decline in various rural areas. This article attempts to discuss the role of the community in Bugel Village, Tangen District, Sragen Regency in maintaining and preserving the tradition of mutual cooperation amid social changes. This study uses a descriptive qualitative approach with a literature study method. The data collected came from various journals, scientific articles, and documents related to mutual cooperation and the role of the village community. The results of the study show that the community of Bugel Village is still actively practicing mutual cooperation in various activities such as community service and village development. Mutual cooperation serves as a way to save costs, increase labor, and strengthen social relations among residents. However, there are several challenges, such as declining participation among the younger generation and the emergence of individualistic attitudes. Therefore, continuous efforts are needed through routine village activities and cultural approaches so that mutual cooperation remains relevant and sustainable amid changing times.